2014
DOI: 10.1002/jsfa.6929
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fruit quality, bioactive compounds and total antioxidant activity of flat peach cultivars

Abstract: Overall data suggested that the flat white-fleshed nectarine Planet 1, the yellow-fleshed nectarine Mesembrina and the yellow-fleshed peach Ufo 6, because of their profiles in terms of soluble solids content, titratable acidity and bioactive compounds, have the greatest potential to meet current consumer requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 29 publications
0
20
2
2
Order By: Relevance
“…While 'BRS Kampai' had a mean of 17.76 mg rutin on 100 g -1 pulp. These values are below those found by Di Vaio et al (2014), who obtained between 32.78 to 80.92g of quercetin equivalent Kg -1 of fresh weight for different peach and nectarine cultivars. The same authors did not observe any relationship between fruit pulp colour and high flavonoid contents.…”
Section: Biochemical Characterization Of Fruitscontrasting
confidence: 79%
See 1 more Smart Citation
“…While 'BRS Kampai' had a mean of 17.76 mg rutin on 100 g -1 pulp. These values are below those found by Di Vaio et al (2014), who obtained between 32.78 to 80.92g of quercetin equivalent Kg -1 of fresh weight for different peach and nectarine cultivars. The same authors did not observe any relationship between fruit pulp colour and high flavonoid contents.…”
Section: Biochemical Characterization Of Fruitscontrasting
confidence: 79%
“…Evaluating the antioxidant activity in fruits of different peach cultivars, Di Vaio et al (2014), obtained in white pulp fruits values between 4.25 and 4.37 mmol Trolox equivalent Kg -1 of fresh weight, and to yellow pulp fruits between 4.22 and 4.91 mmol Trolox equivalent Kg -1 of fresh weight. According to the same authors, the lack of standardization between methodologies used for conducting this type of analysis is a factor that hinders the comparison between antioxidant activity in foods through data from other studies found in the literature.…”
Section: Biochemical Characterization Of Fruitsmentioning
confidence: 99%
“…Several researchers have demonstrated the effectiveness of PCA plotting in genetic classification, evaluation of fruit quality, biodiversity and postharvest studies . This was the case in the current experiment, since PCA scores have produced useful information on fruit quality in relation to treatments.…”
Section: Resultsmentioning
confidence: 54%
“…Antioxidant compounds, such as carotenoids, flavonoids, vitamin C [L‐ascorbic acid (AsA)], and 5‐hydroxy‐tryptophan, are regarded as determinants of quality in berries (1, 2). Berry color is an important external indicator of berry quality (3), and deeply colored berries tend to have more vitamins and antioxidants.…”
mentioning
confidence: 99%